Exploring patient and professional perspectives on implementing pharmacogenomic testing in the UK primary care setting and estimating the cost-effectiveness: a mixed-methods study protocol - Asam Latif; Dyfrig A Hughes; Stephen Timmons; Anthony Avery; Sadaf Qureshi (BMJ Open)
Introduction Pharmacogenomic testing could potentially reduce the number of adverse drug reactions and improve treatment outcomes through tailoring treatment to an individual’s genetic makeup. Despite its benefits and the ambitions to integrate into routine care, the implementation of pharmacogenomic testing in primary care settings remains limited. This study aims to qualitatively explore the views of healthcare professionals (HCPs) and patients on implementing pharmacogenomic testing in the UK National Health Service (NHS) primary care setting and to estimate the cost-effectiveness of service-delivery implementation by comparing different HCPs’ models of care.Method This study consists of three workstreams (WS). WS1 is semi-structured interviews with General Practitioners, pharmacists, nurses and patients (24 participants) to explore implementation issues, including the perceived barriers and facilitators to delivering a pharmacogenomic service. WS2 consists of focus groups (between 24–36 participants) with genomic experts to develop practical pharmacogenomic-guided clinical pathways for primary care. WS3 will estimate the cost-effectiveness of implementing pharmacogenomic testing when led by different HCPs incorporating parameters from the literature, expert opinions, as well as data from WS1 and WS2.Analysis Thematic analysis will be used to analyse the qualitative data from WS1 and WS2, mapping findings onto the Consolidated Framework for Implementation Research domains, which will also be used as the theoretical framework. WS3 will be a decision-analytic model developed in Microsoft Excel to compare the cost-effectiveness of pharmacist-led, GP-led, nurse-led or multidisciplinary pathways.Ethics and dissemination This study has been approved by the NHS Health Research Authority and Health and Care Research Wales (24/PR/1088). Findings will be disseminated through peer-reviewed publications, conference presentations and engagement with NHS policymakers and Genomics England.